Comparing the cost-effectiveness and clinical effectiveness of a new community in-reach rehabilitation service with the cost-effectiveness and clinical effectiveness of an established hospital-based rehabilitation service for older people: a pragmatic randomised controlled trial with microcost and qualitative analysis – the Community In-reach Rehabilitation And Care Transition (CIRACT) study - Sahota, Opinder; Pulikottil-Jacob, Ruth; Marshall, Fiona; Montgomery, Alan; Tan, Wei; Sach, Tracey; Logan, Pip; Kendrick, Denise; Watson, Alison; Walker, Maria; Waring, Justin (NIHR Journals Library, 2016)
Background: Older people represent a significant proportion of patients admitted to hospital as a medical emergency. Compared with the care of younger patients, their care is more challenging, their stay in hospital is much longer, their risk of hospital-acquired problems is much higher and their 28-day readmission rate is much greater.